2018
DOI: 10.7326/m18-1523
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Preventing Thromboembolic Events in Patients With Atrial Fibrillation

Abstract: Background: The comparative safety and effectiveness of treatments to prevent thromboembolic complications in atrial fibrillation (AF) remains uncertain. Purpose: To compare the available treatment strategies in patients with AF. Data Sources: English-language studies in multiple databases from January 1, 2000, to February 14, 2018. Study Selection: Two reviewers independently screened citations for studies examining treatments for stroke prevention in patients with AF. Data Extraction: Two reviewers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Recent meta-analyses of observational studies showed either a similar or a lower risk of stroke associated with DOAC use compared to warfarin, with heterogeneity regarding which DOAC was associated with reduced risk of stroke. 10,13,14 A large observational study from Sweden, in which warfarin-exposed patients had a time in therapeutic range of international normalized ratio measurements of Research 71.4%, also showed a similar HR for ischemic strokes for DOACs and warfarin. 34 In their recent observational studies, however, both Lip and colleagues 35 and Graham and colleagues 36 reported decreased risk of stroke with all 3 DOACs compared to warfarin.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent meta-analyses of observational studies showed either a similar or a lower risk of stroke associated with DOAC use compared to warfarin, with heterogeneity regarding which DOAC was associated with reduced risk of stroke. 10,13,14 A large observational study from Sweden, in which warfarin-exposed patients had a time in therapeutic range of international normalized ratio measurements of Research 71.4%, also showed a similar HR for ischemic strokes for DOACs and warfarin. 34 In their recent observational studies, however, both Lip and colleagues 35 and Graham and colleagues 36 reported decreased risk of stroke with all 3 DOACs compared to warfarin.…”
Section: Discussionmentioning
confidence: 94%
“…34 In their recent observational studies, however, both Lip and colleagues 35 and Graham and colleagues 36 reported decreased risk of stroke with all 3 DOACs compared to warfarin. Recent meta-analyses showed similar major bleeding risks with rivaroxaban compared to warfarin, 10,11,13,14 lower or similar major bleeding risk with dabigatran, 10,11,13 and lower major bleeding risk with apixaban. 10,11,13 The finding that is most consistent across the literature is that of lower intracranial bleeds with DOACs than with warfarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, Novel Oral Anticoagulants (NOACs) such as Rivaroxaban might offer a convenient alternative to Warfarin in some thrombotic and thromboembolic disorders [7,8] Some evidence shows that NOACs generally reduce the potential risks of major and fatal hemorrhages, the major adverse event of anticoagulant drugs, compared to vitamin-K antagonists [9][10][11]. Some reports have shown that Rivaroxaban has a therapeutic effect equivalent to Warfarin in deep vein thrombosis and pulmonary embolism [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding associated with anticoagulation therapy remains a major concern for clinicians and patients. Whilst quantification of the risk of bleeding has been inconsistent due to differences in study sample sizes, patient populations and time frames, studies with DOACs in general indicate an increased risk of gastrointestinal hemorrhage and a lower risk of intracranial bleeding compared to warfarin [ 8 ] and with apixaban and edoxaban being superior to rivaroxaban, dabigatran and warfarin in reducing the risk of major bleeding [ 9 ].…”
Section: Introductionmentioning
confidence: 99%